1995
DOI: 10.1149/1.2048641
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Metal‐Sputter Contamination in Ion Implanter for Low‐Temperature‐Annealed, Low‐Reverse‐Bias‐Current Junctions

Abstract: By eliminating metal contamination caused by sputtering events occurring behind the wafer as well as in front of the wafer, we have successfully formed ultrashallow, low-reverse-bias-current n+p junctions by postimplantation annealing conducted at a temperature as low as 450~ Further, we propose that the increased leakage current still present in the absence of metallic contamination is due to the residual damage which is the ion-implantation generated point defects widely distributed in the bulk of silicon. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Special attention has to be given to ion implantation where the effects such as sputtering, [3] cross contamination from previous implantation steps, [4] and mass interference (e.g., BF 2 and Mo [5] ) are often the origin of metallic contamination. Examples of Al sputtering during P þ implantation at 45 keV and As þ at 25 keV, [6] respectively, and Fe sputtering during an As þ implantation at 60 keV, [7] are illustrated in Figure 1. For a detailed analysis, one has to take into account the type of implanted species, the dose, and the energy and the metal that is sputtered away.…”
Section: Metal Contamination and Device Processingmentioning
confidence: 99%
“…Special attention has to be given to ion implantation where the effects such as sputtering, [3] cross contamination from previous implantation steps, [4] and mass interference (e.g., BF 2 and Mo [5] ) are often the origin of metallic contamination. Examples of Al sputtering during P þ implantation at 45 keV and As þ at 25 keV, [6] respectively, and Fe sputtering during an As þ implantation at 60 keV, [7] are illustrated in Figure 1. For a detailed analysis, one has to take into account the type of implanted species, the dose, and the energy and the metal that is sputtered away.…”
Section: Metal Contamination and Device Processingmentioning
confidence: 99%
“…Metal contamination (Tomita et al, 1995) and various forms of cross-contamination between related implantation processes (Haas et al, 1978) are problems of significant concern. Contamination originates primarily from surfaces irradiated by the ion beam, such as process disks, dummy wafers, and various locations on the equipment body.…”
Section: Concentration Concentrationmentioning
confidence: 99%
“…[1][2][3] Most metallic contamination occurs during wafer processing, particularly reactive ion etching and ion implantation [4][5][6] and here it has been reported that metals transported with dopant ion from an ion source or acceleration tube in ion implantation equipment can be deposited on silicon surfaces. 5,6 On the other hand, the behavior of surface metal impurities penetrating by the collision with a dopant ion has not been known. The ion implantation may assist surface metal impurities penetrating the screen films and silicon.…”
mentioning
confidence: 95%